DOT1L‐HES6 fusion drives androgen independent growth in prostate cancer. Issue 9 (8th July 2014) - Annala, Matti; Kivinummi, Kati; Leinonen, Katri; Tuominen, Joonas; Zhang, Wei; Visakorpi, Tapio; Nykter, Matti
<x xml:space="preserve">Abstract</x> Evidence is presented for a case of androgen receptor‐negative prostate cancer driven by a DOT1L‐HES6 fusion gene which directly induces overexpression and pathological activation of HES6.<boxed-text content-type="graphic" id="emmm201404210-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>